Цивільно-спортивне право як підгалузь цивільного права України - Лисенко, Ірина В'ячеславівна; Лисенко, Андрій Миколайович; Перевалова, Людмила Вікторівна; Гаряєва, Ганна Михайлівна (Державний науково-дослідний інститут МВС України, 2022)
Статтю присвячено актуальним питанням реформування цивільного права як галузі права та включення до його структури такої підгалузі, як спортивне право. Цивільно-спортивне право, виступаючи складовим елементом цивільного права, являє собою підгалузь українського права, яка регулює відносини між учасниками цивільно-спортивних відносин: фізичними та юридичними особами, державою, територіальними громадами, іноземними державами та іншими суб'єктами публічного права у сфері фізичної культури та спорту.

The article is devoted to topical issues of reforming civil law as a branch of law and including in its structure such a sub-branch as sports law. The introduction of a new legal entity into the system of civil law of Ukraine – sports law, which regulates the activities of subjects of private law relations in the field of rules and regulations, is substantiated. They determine the legal status and ensure the protection of the interests of individuals on the basis of legal equality, the absence of their own powers between the subjects. For modern society, sports played an important part in its development. This requires legal regulation of disputes, systematization of sources of sports law, which should harmonize the whole array of regulations in the field of physical culture and sports. Similarly, it would allow the development of curricula to train future specialists in this field and the creation of sports courts in our country. The dominant place in the public life of the state and in particular in sports belongs to human health (this is enshrined in Article 3 of the Constitution of Ukraine). It is recognized as the highest social value in the state. Significant funding in this area leads to the creation and systematization of the system of legal norms governing sports relations. In particular, among the issues that need to be resolved by law are the regulation of the legal status of the athlete, the procedure of sports arbitration, the features of protection of the rights and interests of the subjects of sports relations. To do this, first of all, it is necessary to determine the legal sources of civil sports law. The branch of civil sports law, acting as an integral part of civil law, is a subbranch of Ukrainian law that regulates relations between participants in civil sports relations: individuals and legal entities, the state, local communities, foreign states and other public law entities in the field of physical culture and sports. Civil sports law has its own sources of law. This is the basis for its inclusion in the structure of civil law of Ukraine. Systematization of civil sports law should be carried out by codification. This is due to the presence of a large number of sources of sports law. It will also help to eliminate the gaps and contradictions that currently exist in the regulations governing the relationship between physical culture and sports. Sports law will meet international (European) standards; the legal status of professional athletes will become more protected; intensified research in the field of private law regulation of public relations that arise in the field of physical culture and sports; a competitive Olympic reserve will be formed; additional opportunities will be created to involve the general public, especially minors, in physical education and sports.
Civil and sports law as a sub-branch of Ukrainian civil law
Keywords: цивільне право; спортивне право; спорт; джерела спортивного права; норми права; прецедент; правовий звичай; civil law; sports law; sports; sources of sports law; norms of law; precedent; legal custom